Participation Of Men Of Childbearing Age In Vasectomy Contraception In Kupang Tengah Subdistrict In Kupang District - Koban, Maria Y. P. W; Takaeb, Afrona E. L; Ndoen, Honey Ivon (Timorese Journal of Public Health, 2024)
Vasectomy is a stable contraceptive technique for men by cutting the sperm ducts (vas deferens) that carry sperm out of the testicles. Central Kupang Regency is one of the districts with the lowest coverage of vasectomy contraception, namely there are only 10 male couples of childbearing age who use vasectomy contraception. This study aims to find out the reasons why men of reproductive age participate or not in the use of vasectomy contraception in Kupang Tengah District, Kupang Regency. This type of research was qualitative with the method of interviewing 10 informants consisting of 4 PUS who used vasectomy KB, 5 PUS who did not use vasectomy KB, and 1 PLKB support officer. Data analysis uses thematic analysis and triangulation. The results showed that husbands' knowledge of male contraception was categorized as lacking, because there were still many husbands who did not know about family planning contraception and the lack of sources of information about vasectomy contraception. Some of the respondents in this study had an attitude of not supporting their husbands in using the vasectomy family planning program, so they did not choose vasectomy contraception. In this study it can be seen that men who have had a vasectomy have a place to live far from the place of health services so it takes a long time. Under these circumstances, men still participate in vasectomy. It is suggested to PLKB officers that in counseling about vasectomy family planning not only among mothers, but also husbands so that husbands understand and understand about vasectomy contraception, so that later husbands have a sense of will and are no longer worried about vasectomy contraception.